2015
DOI: 10.3109/0886022x.2015.1074473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intradialytic exercise on systemic cytokine in patients with chronic kidney disease

Abstract: Background: Immunological dysfunctions and a pro-inflammatory environment are associated with higher risk of cardiovascular diseases in chronic kidney disease (CKD). Physical exercise can be an important anti-inflammatory strategy, but the effects in CKD remain poorly investigated. Objective: Evaluate the acute inflammatory response to intradialytic exercise in the peripheral blood of individuals with CKD. Methods: Nine patients, of both genders, with CKD and allocated in the ambulatory of hemodialysis of Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…A recent systematic review highlighted a lack of understanding of the acute effects of exercise on inflammatory markers in chronic inflammatory diseases [47]. One recent paper reported an increase in IL-10 after HD including 20 min cycling with a similar absence of changes in IL-6 and TNF-α [48]. Another study found no immediate change in CRP after intradialytic resistance exercise despite a decrease in the antioxidant superoxide dismutase [49].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review highlighted a lack of understanding of the acute effects of exercise on inflammatory markers in chronic inflammatory diseases [47]. One recent paper reported an increase in IL-10 after HD including 20 min cycling with a similar absence of changes in IL-6 and TNF-α [48]. Another study found no immediate change in CRP after intradialytic resistance exercise despite a decrease in the antioxidant superoxide dismutase [49].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study by Peres et al indicated that physical activity moderates the plasma levels of inflammatory factors (31). It should be mentioned that our study period was short.…”
Section: Discussionmentioning
confidence: 73%
“…Previously published data reported the peripheral frequency of Natural Killer cells and cytokine levels in response to intradialytic exercise. 7,9 The non-inclusion criteria included patients with severe heart disease, uncontrolled arterial hypertension, thrombosis, ischemic cardiopathy, amputation, excessive pallor, severe dyspnea, femoral fistula, precordial pain, orthopedic or neurological compromising, and cognitive impairment. Additionally, eight healthy elderly (age between 60 and 80 years) individuals with no apparent diseases (i.e.…”
Section: Methodsmentioning
confidence: 99%